PENGEMBANGAN GAME EDUKASI PADA MATERI TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS X DI SMK NEGERI 5 PADANG - Wahyuni, Sindi Mardia; Mary, Thomson; Pratama, Ade (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research uses Research and Development (R D) research with the ADDIE development model which consists of 5 stages, namely, Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation) and Evaluation (Evaluation). The ADDIE model concept is applied to develop a learning product design. The media validation results obtained an average score of 82.22% in the "Very Valid" category. The material validation results obtained an average score of 84.94% in the "Very Valid" category. Practicality results by teachers obtained an average score of 85.41% in the "Very Practical" category, for practicality results students obtained an average score of 80.17% in the "Very Practical" category. Based on the research results, the development of educational games based on information and communication technology material developed at SMK Negeri 5 Padang was declared valid and practical.